Strengthening the role of microarchitectural stages of embedded systems design - Kolchurin, M.V.; Pinkevich, V.Yu; Platunov, A.E. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
The growing variety of computing systems, the rapid increase in their complexity, their integration into objects and processes of the physical world require a dramatic increase in the productivity of their creators. It is noted that the quality, timing, and degree of reuse of design results in the field of information technologies strongly depend on design methodologies and routes at the stages of choosing and/or creating stacks of platforms, technologies and tools. The most important role belongs to the ways of describing the organization of the computing system at various levels and to the used systems of abstractions. The problem of filling the semantic gap between the conceptual (architectural) level and the implementation levels is still very acute. So, it requires the creation of industrial techniques and design tools at these “intermediate” levels. The paper suggests ways of presenting design solutions that are aimed at a holistic, end-to-end description of both the logic of the computing process organization and the steps, technologies, and tools of the design process. The content and the necessity of the stages of microarchitectural design of computing systems is justified and explained in detail. Classification of projects in the field of information technologies according to the degree of variability of the project platform is introduced. Several concepts representing a set of abstractions for microarchitectural design within projects with great variability are suggested. The following abstractions are described in detail: project, design and aspect spaces, project platforms and cross-level mechanisms. Examples of several proposed abstractions presentations (design documentation tools) of microarchitectural design stages are discussed that are most relevant in the design of computing systems in the “limited resources” model: embedded systems, cyber-physical systems, “edge” and “fog” levels of Internet of Things systems.